2018
DOI: 10.1155/2018/3727521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Handprint Culture Training on Compliance of Healthcare Workers with Hand Hygiene

Abstract: Objective We aimed to study the effect of visual observation of bacterial growth from handprints on healthcare workers' (HCWs) compliance with hand hygiene (HH). Settings Medical and postoperative cardiac surgery units. Design Prospective cohort study. Subject The study included 40 HCWs. Intervention Each HCW was interviewed on 3 separate occasions. The 1st interview was held to obtain a handprint culture before and after a session demonstrating the 7 steps of HH using alcohol-based hand rub, allowing comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The characteristics of the 19 interventional studies are shown in Table II . Of these studies, three were RCTs [ [43] , [44] , [45] ], four were interrupted time series [ [46] , [47] , [48] , [49] ],12 were quasi-experimental studies, and one of them was a multicenter study [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ] Pakistan, Saudi Arabia [KSMC] and Saudi Arabia [KAMC] . The study duration ranged from 10 days [ 48 ] to five years [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the 19 interventional studies are shown in Table II . Of these studies, three were RCTs [ [43] , [44] , [45] ], four were interrupted time series [ [46] , [47] , [48] , [49] ],12 were quasi-experimental studies, and one of them was a multicenter study [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ] Pakistan, Saudi Arabia [KSMC] and Saudi Arabia [KAMC] . The study duration ranged from 10 days [ 48 ] to five years [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The intervention was performed in different departments of the hospital. The highly sensitive areas were ICU units [ 45 , 46 , 51 , 52 , [54] , [55] , [56] , [57] , 59 , 60 ], [ 61 ] Pakistan, Saudi Arabia [KSMC] and Saudi Arabia [KAMC] and surgical wards [ 45 , 51 , 59 ], [ 61 ] Pakistan, Saudi Arabia[KSMC] and Saudi Arabia [KAMC] , while the less sensitive areas were medicine [ 45 , 51 , 52 , 59 ], [ 61 ] Pakistan , emergency [ 51 , 59 ], oncology [ 45 , 48 , 61 ] Pakistan and Saudi Arabia[KSMC] , gynecology and obstetrics [ 44 , 61 ] Pakistan and Saudi Arabia[KSMC] , pediatrics [ 51 , 61 ] Saudi Arabia[KSMC] , and others [ 50 , 51 , 56 , 60 ]. Three studies included all hospital departments [ 47 , 49 , 53 ], while two did not mention study departments [ 44 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations